PENDUGAAN MODEL PERTUMBUHAN DAN PENYEBARAN SPASIAL POPULASI RUSA TIMOR (Cervus timorensis de Blainville, 1822) DI TAMAN NASIONAL ALAS PURWO JAWA TIMUR - Yanto Santosa; Diah Auliyani; Agus Priyono Kartono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
Timor deer is ruminant mammals’ species with high adaptability which enable them to be introduced easily in to new habitat. The animal was experiencing population decrease which put them in the rare status. The research was aimed at the estimation of demographic parameter, population growth model, and the determination of spatial distribution pattern of the timor deer population in Alas Purwo National Park (APNP). Animal inventory was conducted using strip transect method with sample unit of 1.5 km length and 100 m width strips. Analyses were conducted on demography parameter (size and density, sex ratio, birth rate/natality and mortality), spatial distribution pattern, and population growth model estimation. The result showed that timor deer in APNP has population size of 8157 ± 1224 individuals with population density of 0,20 ± 0,03 individuals/ha. Population size in general was 1 – 8 individuals/group. The age structure of the population was progressive population with reproductive sex ratio of 1 : 2.3. Rough birth rate/natality was 0.19, while juvenile and fawn mortality was 0.13 and 0.31. The population was spatially distributed in group. Growth model of Timor deer was logistic model, with population growth rate of 0.22 in 38,844 individuals/year habitat carrying capacity.Keywords: Cervus timorensis, demographic, spatial distribution, growth.